The Role Of Bartender On Moctail Quality And Guest Satisfaction At Onyx Lounge Four Points Hotel By Sheraton Medan - Samudra Ginting; Dewi Shinta Wulandari Lubis (SEAN Institute, 2024)
This study aims to examine the role of bartenders in the quality of mocktails and guest satisfaction at Onyx Lounge Hotel Four Points by Sheraton Medan. Onyx Lounge offers food and beverage services, including mocktails, with comfortable indoor and outdoor areas for guests. The quality of mocktails is greatly influenced by the skills, creativity, and consistency of bartenders in mixing drinks. The research method used is descriptive qualitative, with data collection techniques through observation, interviews, and literature studies. The results of the study indicate that bartenders play an important role in maintaining the quality of mocktails, especially in terms of manufacturing techniques, creativity in creating new mocktail variations, and good interaction with guests. However, differences in presentation standards are still found among bartenders. Therefore, it is necessary to improve operational standards to ensure the consistency of mocktail quality. Guest satisfaction is also influenced by friendly and efficient bartender service. In conclusion, the role of bartenders at Onyx Lounge Four Points by Sheraton Medan has a significant effect on the quality of mocktails and guest satisfaction, but still requires improvement in presentation standards.